Anemia in Asthmatic Females Exaggerates the Severity of Inflammation in Asthma by Inducing Dyslipidemia, High levels of IgE and Absolute Eosinophil count: Role of anemia on female asthmatic patient’s lipidemia, IgE and eosinophil count - Rashid, Haji Muhammad; Khan, Mudassar; Jamal, Muhammad; Shah, Wisal (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
The objective of the study was to investigate the effects of anemia on severity of inflammation in asthmatic females with the assessment of dyslipidemia, IgE and absolute Eosinophil count. Study was performed at Pathology Lab of Asia Diagnostic Center, Blue area Islamabad Pakistan. Total 100 asthmatic Females (Group 1) and 100 normal females as control (Group 2) were enrolled in this study. Hemoglobin (Hb) levels, Total leukocyte count, Lipid profile, serum IgE and Eosinophil count were analyzed in Group 1 and Group 2. Group 1 was sub divided in to two groups. Group 1a asthmatic females with anemia and Group1b asthmatic females without anemia. Triglycerides (TG) and very low density lipoprotein (VLDL) with mean value 139.8 ± 27.9 and 23.6 ± 6 in Group 1a were not significantly different with p-value >0.05 from Group1bwith mean value of TG 137 ± 25.5 and VLDL 25.9 ± 5.8. Cholesterol and low density lipoprotein (LDL) were significantly high in Group 1a than Group1b with p-value <0.05. HDL levels in Group 1a were significantly lower than Group1b with the p-value 0.017. Markers of severity of inflammation in asthma, IgE and Absolute Eosinophil Count were also high in Group 1a with p value 0.0297 and <0.0001 respectively from Group1b. The strongest negative correlations ware observed for LDL - 0.60. IgE - 0.61 and absolute eosinophil count -0.99 with Hb levels in Group 1a ,which indicate that anemia exaggerate the severity of inflammation in asthma as well as dyslipidemia in anemic asthmatic females. From our study it was concluded that when anemia is present in asthmatic females it will exaggerate the severity of inflammation in asthma by inducing dyslipidemia, high eosinophil count and high level of IgE.